Cytokine Profile in Patients with Rheumatoid Arthritis - Manhal, Falah S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Cytokines produced by inflammatory cells play a pivotal role in synovial inflammation and joint destruction in rheumatoid arthritis. Patients and Methods: The cytokine serum levels were measured by EASIA (Enzyme amplified sensitivity immunoassay) in sera from 50 RA patients, and 40 healthy donors. Cytokine levels were compared in different RA subpopulations (positive or negative rheumatoid factor (RF), long term or recent onset disease, high or low disease activity). In addition, the possible association with other demographic and clinical parameters (gender, age, etc) was also analyzed. Results: It was demonstrated that IL-2, IL-6 and IFN-δ levels were elevated in serum samples of RA patients as compared with apparently healthy controls. Maximum elevation of TNF-α was recorded in a few number of patient’s sera. There were non significant differences between control and RA patient groups in serum TNF-α level. Conclusions: Assessing the serum IL-2, IL-6, IFN-δ and TNF-α levels may be helpful in the confirmation of the RA activity. Due to the chronic course of this disease, other inflammatory markers must be identified in order to provide early therapeutic strategies to these patients.